Contemporary Song Folklore of the Kazakhs of the South-West Zhetysu: The Experience of Musical and Regional Research - Babizhan, B.Z.; Berdibay, A.R.; Baisakalova, A.B.; Chukmanov, Y.T.; Ulkenbaeva, A.N. (International Journal of Criminology and Sociology, 2021)
Kazakh music and dance has many unique features but also has many things in common with the music and dance of Mongolia and Central Asia. For Kazakhs the summer has traditionally been the best time for merry-making. They often sing and dance during summer nights on the pastures. The relevance of the study is due to the insufficient study of the Kazakh song folklore of the south-western part of Zhetysu, represented by eight districts of the borderland of Almaty and Zhambyl regions with Kyrgyzstan. This article is aimed at identifying the genre composition of the song folklore of the local tradition, the conditions of its existence, as well as the peculiarities of their musical-poetic structure and musical language. The results of this research are a contribution to the musical archeology of Kazakhstan. They can also be used in the study of the stylistic originality of the song folklore of the Kyrgyz and Uzbeks living in the border regions of Kazakhstan and Kyrgyzstan.